1999
DOI: 10.1046/j.1365-2672.1999.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zinc oxide supplementation on the stability of the intestinal flora with special reference to composition of coliforms in weaned pigs

Abstract: M. KATOULI, L.MELIN, M. JENSEN-WAERN, P. WALLGREN AND R. MÖ L LB Y. 1999. The effect of a dietary supplementation of zinc oxide (ZnO) on the stability of the intestinal flora and on the composition of coliforms in weaned pigs was investigated. Faecal floras were characterized by their metabolic activities and fermentative capacity (FC) using the Phene Plate generalized microplate. Coliforms were characterized by conventional enumeration and by the Phene Plate-RS plates. The latter measured FC, phenotypic diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 27 publications
7
106
0
5
Order By: Relevance
“…The reduction of PWD prevalence after pharmacological levels of ZnO may not only be related to direct reduction of pathogenic E. coli in the intestine but can also be associated with the increase of diversity and maintenance of the stability of intestinal flora (Katouli et al 1999;Vahjen et al 2011;Pieper et al 2012;Starke et al 2013). Unlike previous studies, which found an increase in the enterobacterial group including Escherichia coli in the ileum in piglets supplemented with high dietary ZnO (Vahjen et al 2011;Pieper et al 2012), in our ETEC infection model, we did not observe this trend in faecal samples after three weeks of supplementation (Day 21, Table 2) with neither 2500 mg/kg nor 1700 mg/kg ZnO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of PWD prevalence after pharmacological levels of ZnO may not only be related to direct reduction of pathogenic E. coli in the intestine but can also be associated with the increase of diversity and maintenance of the stability of intestinal flora (Katouli et al 1999;Vahjen et al 2011;Pieper et al 2012;Starke et al 2013). Unlike previous studies, which found an increase in the enterobacterial group including Escherichia coli in the ileum in piglets supplemented with high dietary ZnO (Vahjen et al 2011;Pieper et al 2012), in our ETEC infection model, we did not observe this trend in faecal samples after three weeks of supplementation (Day 21, Table 2) with neither 2500 mg/kg nor 1700 mg/kg ZnO.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of zinc is still not fully understood. However, it was found that high dietary ZnO has a positive impact on the stability and diversity of the intestinal flora which contributes to a high colonisation resistance against pathogens and thereby to resistance to diarrhoeal infections and to better growth performance (Katouli et al 1999;Vahjen et al 2011;Pieper et al 2012). Although ZnO has traditionally been included in diets for weaning piglets, its excretion in high amounts represents a hazard to the environment (Heo et al 2013;Sales 2013).…”
mentioning
confidence: 99%
“…Los niveles más bajos de IgA en el calostro de las cerdas que consumieron alimento adicionado con Met-Zn, se pudo deber al efecto farmacológico del Zn sobre la flora patógena intestinal, disminuyendo o estabilizando su población en el intestino; así como al mantenimiento de la integridad intestinal, lo que evita que ésta sea permeable a las endotoxinas bacterianas. Se ha informado al respecto que la suplementación con ZnO se ha asociado con una disminución en el traslado de bacterias desde el intestino delgado a los nódulos linfáticos mesentérico (Huang et al, 1999) y con un incremento en la estabilidad y homogeneidad en la población de coliformes (Kautouli et al, 1999); así como protegiendo la integridad de la mucosa intestinal (Pearce et al, 2015).…”
Section: Resultados Y Discusiónunclassified
“…Zinc supplementation has been shown to prevent or alleviate diarrhoea in piglets [30,31,56], to maintain stable levels of the intestinal flora and diverse coliforms that may compete with diarrhoegenic strains for colonisation sites [35] and to reduce translocation of pathogenic bacteria from the small intestine to the mesenteric lymph nodes [30]. However, Li et al [41] did not observe any effect on the microflora collected from the digesta and faeces of piglets after 11 days of high dose ZnO supplementation.…”
Section: Protection Against Pathogensmentioning
confidence: 99%
“…However, these studies did not investigate whether the effect of zinc supplementation is dependent on the physiological conditions of the cells and on the presence of inflammation induced by bacteria, and whether this effect is associated with a decrease of bacterial infection. Indeed, some authors did not find a reduced number of E. coli in the faeces of pigs treated with ZnO [31,35].…”
Section: Maintenance Of Barrier Integritymentioning
confidence: 99%